Grupos Interativos: uma proposta educativa - Rodrigues, Eglen Sílvia Pípi (Universidade Federal de São Carlos, 2010)
The research presented here sought to investigate a proposed educational differentiated teaching and learning called Group Interactive that exists in schools that are Learning Communities. The Interactive Group is a transformation of the class, where small heterogeneous groups, under the criteria of income, ethnicity, gender, etc. are formed. The choice of this topic is justified by the fact that we consider Interactive Groups a possible alternative way that allows students to improve school social live and also accelerate their learning. Through this practice is to realize the dialogic learning, because it is the result of different interactions that produce equal dialogue, a dialogue of equals, whose intention is reached by the consensus on the basis of claims to validity. The increase of interactions in the classroom benefits both learning and solidarity among the students, enabling them to overcome the condition of school failure. The objectives were proposed to respond how to the processes of interaction afforded by Interactive Groups occur and how they contribute to the learning of different people participating in this practice. These objectives sought to analyze the interaction processes existing in Interactive Groups, from the perspective of people involved (teachers, students, volunteers); verify the potential for interaction and dialogue between the different educational agents, aiming at maximum learning for all students; identify and analyze the learning acquired by those involved through interactive processes in this educational practice. For the development of this research two classes of grades of education of a local public school in São Carlos / SP Interactive Groups that performed weekly were accompanied. The methodology used for this research was the critical communicative research. The techniques used for data collection were communicative observations; communicative life narratives and communicative group discussions. As regards the theoretical and methodological framework, the main authors and concepts used in the analysis were: the concept of Interaction from Vygotski, Dialogical Learning from Flecha (CREA), Dialogue from Freire, and the concept of mediated activity from Leontiev. This research shows that the practice of inter-group is a tool to strengthen and accelerate the learning of children. This research provided to the Buriti Valley Learning Community an analysis of the importance of ensuring the participation of different people (cultures, ethnicities, social classes, religions, etc..) in the learning process of elementary school. The participation and interaction of the volunteers in the classroom ensures the dialogue in multicultural school, enhances values such as solidarity, facilitates and accelerates the instrumental learning of all students. The format of the dynamics provides more people within the classroom to support the work of the teacher, by increasing and improving the interactions, contributing with the increasing the opportunities for the students to learn.
Keywords: Aprendizagem; Conhecimento; Diálogo; Grupos sociais; Interação social; Ensino-aprendizagem; Learning; Knowledge; Dialogue; Social group; Social interaction; CIENCIAS HUMANAS::EDUCACAO